An impact of CYP3A4 *1B polymorphism on rifampicin metabolism - H. O. Poludenko; P. B. Antonenko (Journal of Education, Health and Sport, 2017)
Until now, the enzyme systems responsible for biotransformation of the antituberculous drug rifampicin remain unknown. The aim of research was an investigation of the candidate enzymes involved in the biotransformation of rifampicin using the computer system PASS and an experimental study concerning the effect of the polymorphism of the biotransformation gene CYP3A4 *1B on the level of rifampicin in the blood of patients with pulmonary tuberculosis (РTB).